2014
DOI: 10.30539/iraqijvm.v38i1.260
|View full text |Cite
|
Sign up to set email alerts
|

Seropathological Diagnosis of Toxoplasma gondii in Stray Cats in Baghdad Province

Abstract: The current study was performed an investigation in seropositive stray cats with Toxoplasma gondii and to correlate the results of pathological lesions with seropositive results of the cats. To achieve these goals, fifty blood samples and specimens from internal organs (liver, spleen, brain, kidney, intestine and lung) of stray cats were collected from different area of Baghdad Province during the period 1.10.2011-1.10.2012. Seropositive ELISA-IgG was demonstrated that 66 % of stray cats while female expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Moreover, the difference might not have been statistically significant due to the transfer of maternal antibodies in cats younger than six months, which increased their seropositivity. Similarly to our results, many researchers have not established any correlation between increased age and seroprevalence [50,61,63,64,71,76], although, in some of those studies, a non-significant increase in seropositivity in older cats was depicted [63,71].…”
Section: Factors Influencing T Gondii Seropositivity In Cats Have Bee...supporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, the difference might not have been statistically significant due to the transfer of maternal antibodies in cats younger than six months, which increased their seropositivity. Similarly to our results, many researchers have not established any correlation between increased age and seroprevalence [50,61,63,64,71,76], although, in some of those studies, a non-significant increase in seropositivity in older cats was depicted [63,71].…”
Section: Factors Influencing T Gondii Seropositivity In Cats Have Bee...supporting
confidence: 80%
“…Conversely, some studies observed higher seropositivity in female cats [45,[74][75][76]. The explanations provided were that females have different behaviours than males, and may wander more based on the season [45] or hormonal imbalances [76].…”
Section: Factors Influencing T Gondii Seropositivity In Cats Have Bee...mentioning
confidence: 98%
See 1 more Smart Citation
“…However, in our study based on the results of univariate analysis, females were significantly more likely to be T.gondii -seropositive compared to male cats. Our finding is consistent with other studies that showed higher seropositivity in female cats and could be explained by the fact that females behave differently than males and may roam more based on the season or hormonal imbalances [ 53 , 57 , 59 , 60 ]. However, female gender was not statistically significant in the multivariate model.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies, and it may be explained by the fact that older cats have more time to be exposed to the parasite [ 50 , 55 , 56 ] and not because older cats may have a weaker immune response, which can make them more susceptible to T. gondii infection and more likely to develop antibodies against the parasite. Although seropositivity increases with age, indicating postnatal transmission of T. gondii , in a study published in 2014, the authors showed a significantly higher seroprevalence of T. gondii in young cats aged 2 months (100.0%) compared to adult cats (66.8%) [ 57 ]. This finding probably was due to the transfer of IgG maternal antibodies through the colostrum [ 50 ].…”
Section: Discussionmentioning
confidence: 99%